EFFECT OF 2008 AND 2016 U.S. PRESIDENTIAL ELECTION IN THE INDONESIAN STOCK MARKET - Evelyn Evelyn; Sautma Ronni Basana (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
The U.S. Presidential election was an event that received widespread attention across the globe. In the 2008 presidential campaign, Barrack Obama nominated to be the first black President. In 2016, Hillary Clinton potentially becomes the first woman President in American history, while the other candidate, Donald Trump, made some unpopular and controversial proposals. The purpose of this paper is to analyse whether the 2008 and 2016 election were considered as the relevant information in the Indonesian Stock Market (IDX). The daily closing prices of all all share listed in IDX would be examined used event study method. The results provide insight about the responsiveness of IDX participants to the U.S. Presidential election event that could be used in decision making.